Acute coronary syndrome with ST segment elevation in a patient with Addison disease: Case report and brief review of physiopathological mechanisms: A case study - Maranduca, Minela Aida (Exp Ther Med, 2020)
The adrenal gland serve important roles in the modulation of the immune response, the adjustment of blood pressure, the stress reaction via glucocorticoids and the hydroelectrolytic balance via mineralocorticoids. Primary adrenal insufficiency, known as Addison disease, is characterized by a decrease in glucocorticoid secretion (cortisol) and, more rarely, by a hyposecretion of mineralocorticoids (aldosterone). The production of cortisol, which is a hormone that helps the body respond to stress, is regulated in the brain, the hypothalamus and the pituitary gland. The hypothalamus stimulates the pituitary gland to produce adrenocorticotropic hormone, which stimulates cortisol production from the adrenal gland. If left untreated, Addison disease has a high mortality rate. Corticotherapy used in the treatment of Addison disease is associated with a certain cardiovascular risk. The proatherogenic effect of corticoids is based on the chronic inflammatory response of the vascular wall to a series of events. The aim of the current case report was to review the pathophysiological mechanisms and interactions that may lead to the onset of acute coronary syndrome with ST elevation in a patient with Addison disease.